(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the age of globalization, communication across borders has dramatically influenced the development of languages worldwide. The Uzbek language, with its deep historical and cultural roots, is also undergoing transformation due to the spread of global communication channels. This article explores how international media, digital technology, migration, and intercultural interaction have contributed to the evolution of the Uzbek language. While such exposure offers access to global knowledge and innovation, it also presents risks such as language erosion and cultural homogenization. This study highlights both the positive and negative effects of global communication and provides insights into maintaining linguistic identity in a rapidly changing world.